PENDIDIKAN POLITIK BAGI PEMILIH PEMULA SEBAGAI MOTOR GENERASI MUDA DALAM PENINGKATAN PARTISIPASI DAN KESADARAN POLITIK - cholillah suci pratiwi; Arfa'i Arfa'i (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities (PKM) in the form of political education for novice voters as the motor of the younger generation in increasing political participation and awareness at the University of Jambi are aimed at: 1) Increasing students' knowledge and understanding as the motor of the younger generation in increasing political participation and political awareness in the environment. Jambi University thereby increasing participation in politics; 2) There is an active participation from stakeholders, in providing political education for students as the motor of the younger generation in increasing political participation and political awareness within the Jambi University, both in the form of counseling and socialization as well as regular scheduled social gathering activities for political education for the community in the District. Alam Barajo; 3) Establishment of forums and facilities for public political education in the form of political socialization for students at Jambi University. PKM activities are carried out through lecture, discussion, and audio visual methods. The stages of implementing political education activities are carried out through the planning stage and the approach stage. Based on the results of the implementation of PKM activities in the form of political education for novice voters as a motor for the younger generation in increasing political participation and awareness at the University of Jambi, it can be concluded that this political education activity provides new enlightenment and knowledge for the millennial generation to participate and be aware of politics by increasing knowledge. and the understanding of students as the motor of the younger generation in increasing political participation and political awareness in the Jambi University environment so that it has an impact on increasing participation in politics.